2014
DOI: 10.15605/jafes.029.02.06
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Oral Calcium Supplementation on Lipid Profile and Atherogenic Index of Plasma

Abstract: Objective. To assess the effect of oral calcium supplementation on lipid profile and atherogenic index of plasma (AIP).Methodology. This study was undertaken in 28 centrally obese male subjects [age 26.4 (6.5) years], BMI 31.6 (4.7) kg/m 2 , WC 99.4 (6.4) cm. All participants received six tablets of CaCO 3 (250 mg of elemental calcium/ capsule, for a total of 1500 md/day) for 8 weeks. Serum lipid profile including triglyceride, total cholesterol, HDL-C, LDL-C was measured at baseline and after intervention. AI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…Calcium helps in the formation of insoluble soap with esterified fatty acids. This complex becomes more water soluble and readily gets eliminated from body via feces [17]. In one investigation it was found that micronutrients (zinc, manganese and copper) potentiate the antioxidant activity of super oxide dismutase, as SOD is involved in neutralizing lipid peroxides [18].…”
Section: Discussionmentioning
confidence: 99%
“…Calcium helps in the formation of insoluble soap with esterified fatty acids. This complex becomes more water soluble and readily gets eliminated from body via feces [17]. In one investigation it was found that micronutrients (zinc, manganese and copper) potentiate the antioxidant activity of super oxide dismutase, as SOD is involved in neutralizing lipid peroxides [18].…”
Section: Discussionmentioning
confidence: 99%
“…Shidfar et al (2010) also found the beneficial effect of calcium supplementation (1,250 mg elemental calcium/day) against the changes in lipid profile by lowering the TC, LDL-C, and apolipoprotein B in overweight men which further prevented the risk of CVD. Sein and Latt (2014) observed that when obese male subjects were provided with calcium supplementation (1,500 mg/ day) for 8 week there was a significant decrease in serum triglyceride (TG) level and increase in HDL-C level which reduced the risk of atherosclerosis because hypertriglyceridemia activates the hepatic lipase which degraded the HDL-C. So, the improvement in lipid profile in response to dietary calcium not only prevented the risk of dyslipidemia, but also delay the onset of CVD.…”
Section: Effec T Of D Ie Tary C Alci Um On Hypertens Ionmentioning
confidence: 99%
“…The possible mechanisms regarding the beneficial role of high calcium diet against CVD were mediated by improving the several metabolic risk factors like obesity, adiposity, weight gain (Kaluza et al, 2010;Shidfar et al, 2010), lipid profile (Michaelsson et al, 2013;Sein & Latt, 2014), and blood pressure (Shidfar et al, 2010;van Mierlo et al, 2006). At the same time, low calcium intake is associated with secondary hyperparathyroidism (Khan et al, 2015), which promoted vascular calcification thereby stimulating the risk of CVD (Nilsson et al, 2002;Vestergaard et al, 2003).…”
Section: Ard I Ova Scul Ar D Is E a S E S And D Ie Tary C Alci Ummentioning
confidence: 99%